Act of Resistance against Government Policies in Slavery as Reflected in Uncle Tom’s Cabin - Anugrah Murtini (Sekolah Tinggi Agama Islam Negeri Majene, 2020)
The aims of this research were to find the implementation of government policies toward the AfricanAmerican slaves in America and act of resistance against slavery system as reflected in the novel Uncle Tom’s Cabin. The research employs a descriptive qualitative method by applying sociological approach in analyzing Uncle Tom’s Cabin with reference to Wellek and Warren on the relationship between literary work and social context in which it was written. Data sources are primary and supporting data. The primary data are taken from Uncle Tom’s Cabin, and supporting data are taken from the books, journals, articles, and some sources from internet. In this novel, the researcher found that; 1) Government policies toward the African-American slaves reflected in Uncle Tom’s Cabin are Slave Codes 1705 and Fugitive Slave Act 1850 2) the act of resistence by the slaves against slavery system reflected in this novel is passive resistence. Passive resistences are shown by the characters of the slave such as runnaway, tell a lie, and protesting the authority of their owner.